Unearthing key drivers of knowledge leakage. (21st February 2007) - Mohamed, Souad; Mynors, Diane; Grantham, Andrew; Chan, Paul; Coles, Rhoda; Walsh, Kathryn
Intellectual capital such as skills, experience and the critical knowledge of employees is essential for organisations' success. For organisations to use intellectual capital to their best advantage, the concept of Knowledge Leakage, in its positive and negative form needs to be understood. Knowledge or experience leaking away from its origin may lead to a loss of competitive advantage for an organisation. Presented here is the initial assessment of in-depth interviews, with employees of manufacturing and services organisations, aimed at investigating the main drivers of knowledge leakage as a function of firm and inter-firm activities. As a result, organisations' interactions with four key drivers of knowledge leakage have been identified; namely, suppliers, customers, competitors and people. This paper discusses these key drivers and the resulting knowledge leakage with an integrated approach to knowledge 'loss' and 'gain'.